Diagenetic controls on the quality of the Middle Permian Lucaogou Formation tight reservoir, southeastern Junggar Basin, northwestern China. (July 2019) - Liu, Yuming; Ma, Ke; Hou, Jiagen; Yan, Lin; Chen, Fuli
Highlights: The origins of authigenic minerals and diagenetic types got a detailed analysis. The diagenetic events and cementation, dissolution stages were revealed. The effect of diagenesis on sweet spots was evaluated through various methods. Abstract: The Middle Permian Lucaogou Formation, in the southeastern part of the Junggar Basin in China, is a typical tight oil reservoir with low to medium porosity (average 11.2%) and ultra-low permeability (average 0.01 mD). Here, we investigate Lucaogu Formation reservoir diagenesis and its impact on reservoir quality to effectively explore, appraise, and develop this complex tight oil reservoir. Core and thin section analyses, scanning electron microscopy, X-ray diffraction (XRD), electron probe analyses, fluid inclusions, isotopic analysis, pressure-controlled mercury injection, rate-controlled mercury injection, and micro-nanometer X-ray computer tomography (CT) imaging were performed on core samples from the Lucaogou tight reservoir. The sweet spots in the Lucaogu Formation are composed of siltstone, tuffaceous siltstone, and silty dolomite, which underwent two stages of carbonate cementation (primarily calcite, dolomite, and ankerite), clay mineral alteration and dissolution, and one stage of quartz cementation. The major authigenic mineral cements (derived from the original formation water, clay mineral alteration, dissolution of acid-soluble components, and the compaction and drainage of the interbedded mudstone) are also a probable source of ions. It is likely that oil emplacement occurred after quartz cementation and the first stage of carbonate cementation and feldspar dissolution, but before the second stage of calcite cementation and feldspar dissolution. Organic acids produced during hydrocarbon generation contributed to the dissolution of the feldspar and tuffaceous components, locally preventing a decrease in porosity by concurrent cementation and compaction. Carbonate cementation decreased the porosity and permeability of the silty dolomite substantially; in the siltstone, decreased permeability is largely attributed to cementation of clay minerals. The pore structure of the sweet spot is controlled not only by the various cementation events, but also by other geological factors, such as heterogeneous dissolution of the tuffaceous component.